MODERN GUIDELINES OF DENTAL EDUCATION DEVELOPMENT IN UKRAINE - Kulbshna, Ya.A. (Continuing Professional Education: Theory and Practice, 2023)
In the article discusses the problem of defining the key landmarks of modern dental education based on the analysis of the experience of European countries and own research. The need of replacement the educational paradigm from the traditional to competentive and the estimating of learning outcomes was analyzed. The review of scientific literature and own research allowed to establish the doctor's - dentist professional competence components. It consists of such components: motivative - іt importance due to the complexity and responsibility of medical activity, which can do only motivated personAmong the reasons were investigated, the highest, but obviously insufficient, are indicators of the importance of moral values, which positively characterizes the moral image of future doctors. In second place - the commercial business, and the lowest - those which characterize the motivation to for investigating the global scientific and practical problems., gnoseological - reflects the level of a set of knowledge that is the foundation of any professional activity and which actualized within competence, praxeological - determines the possibility of the introduction of practical knowledge and skills in professional activity, which is particularly important for the doctor - dentist. Scientific research determined that it is appropriate to apply the basics of praxeology, which greatly expands the approach to practice, particularly in the area of its organization, planning, forecasting results , deontological - provides the formation of appropriate behavior, moral and psychological aspects of the doctor, international - determines readiness for professional work in an international society, knowledge of foreign languages, the level of international knowledge and skills, tolerance to other nations. Not available for most domestic future professionals with the low level of knowledge of foreign languages, what leading in turn to the impossibility of introducing the principle of academic mobility. Is advisable to issue the «Diploma Supplement» for students with an completely formed international component of professional competence; evaluative - the dominance in dental education the approach to students self - estimation their future educational achievements. That allows to assign responsibility for the quality of education on the student; selfdeveloping provides self-movement of the future doctor to continuous professional self-development, because in the present time of dynamic change of knowledge and receiving large flow of information, even the best training cannot provide long life knowledge. The formation of this component primarily provides continuous professional learning and development. Established, that level of the professional competence formation in students of six medical Universities in Ukraine and one of Belorus is not high enough and have to be increased.